Open Space Technology : a User's Guide. - Owen, Harrison (Berrett-Koehler Publishers, 2008)
Open Space Technology is a methodological tool that enables self-organizing groups of various sizes to deal with hugely complex issues in a very short period of time. Authored by the originator of Open Space Technology, this work presents a user's guide that details what needs to be done before, during, and after an Open Space event.